2018
DOI: 10.6000/1929-4247.2018.07.04.8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Weight Status on Social-Emotional Skills of Adolescents

Abstract: Obesity, which can occur due to numerous causes especially from genetics to nutrition disorders, is a major problem not only for adults but also for children. Childhood obesity causes acute and chronic physical problems in children, but physical effects of obesity, as well as psycho-social effects on children, is a substantial issue. This study was conducted to analyze the effect of different weight status on social-emotional skills of adolescents. The research group comprised 189 female and 194 male of 383 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies have shown that obese children experience various psycho-social problems in this context; overweight and obese adolescents have more negative experiences in social and emotional terms [6,7]. Various studies have shown that overweight and obese adolescents' social-emotional learning skills are lower than of their normal weight peers [1], they have lower self-esteem [7], they are loved less [12], experience more social exclusion [15], and face serious psychosocial complications [9]. Moreover, peer relationships during adolescence are one of the factors that affect adolescents' socialemotional infrastructure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that obese children experience various psycho-social problems in this context; overweight and obese adolescents have more negative experiences in social and emotional terms [6,7]. Various studies have shown that overweight and obese adolescents' social-emotional learning skills are lower than of their normal weight peers [1], they have lower self-esteem [7], they are loved less [12], experience more social exclusion [15], and face serious psychosocial complications [9]. Moreover, peer relationships during adolescence are one of the factors that affect adolescents' socialemotional infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Limited emerging evidence indicates that inter personal factors such as friendships may also have a critical influence on weight outcomes [3]. In this transition period, obesity affects many social-emotional dimensions such as peer relationships, social emotional learning skills, selfesteem, and exclusion in the context of adolescence [1,7,9,12,15]. There is strong evidence that overweight and obesity are associated with poor physical fitness, and children and adolescents who have a poor physical level show low muscular strength and cardiorespiratory endurance, low motor skills and low coordination performance [19].…”
Section: Introductionmentioning
confidence: 99%